Interactive education and anthropometric training for enhanced early stunting detection - Siregar, Nilda Yulita; Sembiring, Arihta Br; Nasution, Eva Mahayani; Gultom, Lusiana; Alfrianne, Alfrianne (Universitas Muhammadiyah Magelang, 2025)
Addressing stunting necessitates an enhanced role for the community, particularly pregnant women and mothers of toddlers, alongside improved skills for cadres in the early detection of toddlers' nutritional status. This community engagement initiative aimed to increase cadres' knowledge of early stunting detection and toddler growth monitoring, as well as to improve mothers' knowledge of stunting prevention. The target participants were pregnant women, mothers of toddlers, and cadres. The activities involved 170 mothers of toddlers, 12 pregnant women, and 15 cadres, and were conducted through interactive education using smart card stunting cards and question-and-answer sessions with pregnant women and mothers of toddlers, as well as anthropometric measurement training for posyandu cadres. Evaluation results demonstrated a significant increase in knowledge among mothers of toddlers (from 66.5% in the moderate category to 93.5% in the good category) and pregnant women (from 66.7% in the moderate category to 100% in the good category) following the stunting education. Furthermore, cadres' skills also improved, with 93.3% of cadres becoming proficient in performing anthropometric measurements.